Hydrodynamics of time-periodic groundwater flow : diffusion waves in porous media - Depner, Joe S.; Rasmussen, Todd C. (Washington, D.C. : John Wiley & Sons, 2017)
Hydrodynamics of Time-Periodic Groundwater Flow' introduces the emerging topic of periodic fluctuations in groundwater. While classical hydrology has often focused on steady flow conditions, many systems display periodic behavior due to tidal, seasonal, annual, and human influences. Describing and quantifying subsurface hydraulic responses to these influences may be challenging to those who are unfamiliar with periodically forced groundwater systems. The goal of this volume is to present a clear and accessible mathematical introduction to the basic and advanced theory of time-periodic groundwater flow, which is essential for developing a comprehensive knowledge of groundwater hydraulics and groundwater hydrology.
Part I: Introduction 1 1 Introduction 3 Part II: Problem Definition 7 2 Initial Boundary Value Problem for Hydraulic Head 9 3 Hydraulic Head Components and Their IBVPs 13 4 Periodic Transient Components 15 5 BVP for Harmonic Constituents 21 6 Polar Form of Space BVP 29 7 Complex-Variable Form of Space BVP 37 8 Comparison of Space BVP Forms 43 Part III: Elementary Examples 45 9 Examples: 1D Flow in Ideal Media 47 10 Examples: 1D Flow in Exponential Media 63 11 Examples: 1D Flow in Power Law Media 89 12 Examples: 2D and 3D Flow in Ideal Media 95 13 Examples: Uniform-Gradient Flow 107 Part IV: Essential Concepts 121 14 Attenuation, Delay, and Gradient Collinearity 123 15 Time Variation of Specific-Discharge Constituent 131 Part V: Stationary Points 149 16 Stationary Points: Basic Concepts 151 17 Stationary Points: Amplitude and Phase 157 18 Flow Stagnation 171 Part VI: Wave Propagation 181 19 Harmonic, Hydraulic Head Waves 183 20 Wave Distortion 199 21 Waves in One Dimension 215 22 Wave Equation 225 Part VII: Energy Transport 231 23 Mechanical Energy of Groundwater 233 24 Mechanical Energy: Time Averages 239 25 Mechanical Energy of Single-Constituent Fields 249 Part VIII: Conclusion 261 26 Conclusion 263 Part IX: Appendices 269 A Hydraulic Head Components 271 B Useful Results from Trigonometry 273 C Linear Transformation of Space Coordinates 275 D Complex Variables 281 E Kelvin Functions 283 Bibliography 291 Index 295
Includes bibliographical references and index.
Keywords: Groundwater flow -- Measurement -- Mathematics